The use of Halliday’s Theme-Rheme on Google’s Privacy Policy Text: A Forensic Linguistics Research - Sabtra Lesmana; Sawirman; Fajri Usman (SOSHUM : Jurnal Sosial dan Humaniora, 2022)
This research was aimed to reveal and explain the violations conducted by Google to its user privacy which is implied through its Privacy Policy Agreement statement by analyzing it with Theme and Rheme proposed by Halliday. This qualitative research was done by applying the documentation recording method in collecting data and the Halliday’s Systemic Functional Linguistics as the basic theory. The result of the data was presented in the table analysis and in the form of descriptive interpretation. The result showed that Google build its clauses with the 4 types of theme construction. From the analyzed clauses, the dominantly built clause is the single constituent with marked theme where “We” is the mostly occurred subject. Yet, Google applied unmarked theme mosty in their clauses. With this dominant occurences of “We”, Google construe its existence as the authority holders of the w hole agreement. The researchers found that similar finite predicator appeared repeatedly such “collect” and “use” in building its clauses. These constitute Google’s strategy in order to force the user’s permission to let Google freely access their privacy. In addition, the operation of the conjunction “and”, extention, expansion and exemplificatory constituents represent the plentiful request of Google related to its user’s information. Those summarized the violation conducted by Google to its user’s privacy. Keywords: clause, forensic-linguistics, misleading-statement, privacy, violation.